Geometry of light the architecture of Arkan Zeytinoglu - Zeytinoglu, Arkan 1968- (Springer, 2011)
This book covers the "built theory" of the architect Arkan Zeytinoglu and "the geometry of light", which describes best his special approach to architecture. Includes essential realizations, a work list and an outlook on buildings to be completed soon.